THE ANALYSIS OF THEMATIC ROLE IN NARRATIVE TEXTS OF SENIOR HIGH SCHOOL TEXTBOOKS - Ririn Marlina (English Review: Journal of English Education, 2012)
Abstract: This paperÂ  analyzed narrative texts of Senior High School textbooks for X Grade, based on Jackendoffâ€™s and Saeedâ€™s theories of thematic role. This research employed aÂ  qualitative research design and the data were ten narrative texts taken from Developing English Competencies and Interlanguage for X Grade. The research Questions involve the ways of thematic role in constructing the sentenceâ€™s meaning in narrative texts and the thematic role that mostly employed. This research revealed that nine kinds of thematic role (Agent, Patient, Location, Beneï¬ciary, Experiencer, Theme, Source, Goal, and Instrument) are available in narrative texts and the role Theme was frequently employed (260 times of 782). Meanwhile, thematic role constructs the sentenceâ€™s meaning in narrative texts by observing the verb and the preposition used in the sentence.Â  Thematic role is a way to describe the role of noun phrase in a sentence, so that thematic role is closely related with the grammatical function. It can be also said that the analysis of thematic role in narrative texts is beneï¬cial for educational participants both teacher and student in order to recognize the sentenceâ€™s grammatical function. Therefore, thematic role helps them to understand the sentenceâ€™s meaning and ï¬nally they can grasp the message in a text.Keywords:Â  Thematic role,Â  Narrative Text, Senior High School, Textbook